2009
DOI: 10.1007/bf03214951
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of small molecules on gold single crystal surfaces

Abstract: Much more work has been carried out on supported gold catalysts (also called "real" catalysts) than on gold single crystal surfaces. However, for fundamental understanding of catalysis by gold, well-defined gold surfaces and controlled conditions using the surface science approach may provide useful information concerning reaction mechanisms and the nature of active centers. This paper presents a brief overview on the work carried out regarding adsorption of several small molecules on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 58 publications
(89 reference statements)
7
50
0
1
Order By: Relevance
“…1b, 2d), in agreement with previous work. [30] This structure is consistent with the length of (2+n)a of features along the [1][2][3][4][5][6][7][8][9][10] direction, as determined by STM. Within this structure model, features with n>2 darker gold atoms contain (n-2) atoms that are perturbed by two oxygen atoms.…”
Section: Stm Contrast On Oxygen On Au(110) and Its Origin Oxygen Atosupporting
confidence: 85%
See 3 more Smart Citations
“…1b, 2d), in agreement with previous work. [30] This structure is consistent with the length of (2+n)a of features along the [1][2][3][4][5][6][7][8][9][10] direction, as determined by STM. Within this structure model, features with n>2 darker gold atoms contain (n-2) atoms that are perturbed by two oxygen atoms.…”
Section: Stm Contrast On Oxygen On Au(110) and Its Origin Oxygen Atosupporting
confidence: 85%
“…Atomic O was created by exposing the surface to ozone since O 2 does not measurably dissociate on crystalline gold. [10,12] Directed ozone dosing was performed using a continuous flow from an ozone generator (Ozone Engineering, model LG-7) to the 1 cm-diameter doser, located ~2 mm from the sample surface. Prior to experiments, several cycles of ozone dosing/annealing were performed to ensure a clean dosing line and sample surface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbonaceous surfaces will typically adsorb hydrogen at around 4-5 kJ/mol 55 whereas metallated surfaces will form a stronger attraction to hydrogen, often between 5 to 50 kJ/mol depending on the metal alloy, 10 surface roughness and crystallite morphology being tested [56][57][58] . Although the adsorption of extended gold surfaces has been demonstrated to be lower than that of other metals such as palladium of platinum 59 , recent work also demonstrated that small gold clusters lead to enhanced adsorption of hydrogen 60,61 . This is demonstrated in Figure 2 and Figure 15 4, where the average NP size was found to be around 52 and 300 nm (Table 1) …”
mentioning
confidence: 99%